SEKOLAH BERWAWASAN GENDER - Wibowo, Dwi Edi (IAIN Pekalongan, 2010)
Abstract:. School is an institution that plays an important role to change the mindset of students, including behaviors that are considered gender bias. Therefore, gender-oriented school that holds a strategic role and function in preparing students for multi intelegensianya to develop optimally without constrained by social values that sometimes gender-biased culture. The process of learning in the classroom that have not been entirely Encouraging active participation Between boys and girls equally, physical school environment that does not answer the specific needs of boys and girls as well as materials teaching materials in general, gender bias, the more clear that face education we do still need to be polished with a gender-responsive approach.